Observation of Effects of Using Alternative Reporting Practices. - Summers, Edward L. (The Accounting Review, 1968)
The article represents a study of one effect on issuers of financial statements in the airline industry which the use of alternative reporting practices has had. A discussion of the results of the study briefly considers the consequences of being able to observe this effect for organized public accounting practice and authority. Capitalists, in such economy in which both good and bad financial statements circulate, face investment decisions in which the results of selecting given alternatives are known with more or less certainty depending on whether the related financial statements are good or bad. The degree of uncertainty can be affected by the form and content management chooses for the financial statements. The author states that firms with bad financial statements would be penalized because capitalists would require a higher return from their equities than from the equities of firms with good financial statements. Financial statements are surely among the devices available for the firm to minimize its purchase of capitalist ignorance within the meaning of the profit-maximization constraint.